EVALUATION OF IN VITRO ANTIOXIDANT AND ANTI-INFLAMMATORY ACTIVITIES OF AEGLE MARMELOS LEAF EXTRACTS - BEGUM HUSSAIN, MUJAWAR SALMA; BASAYYA HIREMATH, MURIGENDRA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The present study aims to investigate preliminary phytochemicals to determine the total phenolic and flavonoid contents and to undergo in vitro antioxidant and anti-inflammatory activities of leaf extracts of Aegle marmelos. Methods: Estimation of total phenols and flavonoids and in vitro antioxidant and anti-inflammatory activities of leaf extracts of A. marmelos was carried out using standard protocols. Results: The highest amount of phenolic and flavonoid content was present in aqueous extract (92.08±0.91 mg/g gallic acid equivalent) and (52.73±0.51 mg/g QE), it also proved to have the most potent antioxidant activity at a concentration of 10 μg/ml (45.57±0.27%) with IC50 values 190 μg/ml. Ethanol extract exhibited the highest anti-inflammatory activity (88.16±0.25) at 100 μg/ml with IC50 values 34.59 μg/ml. Conclusion: It can be concluded that the tested extracts hold significant antioxidant and anti-inflammatory activities. However, further investigation of purified compounds of A. marmelos will enable its medicinal use in the treatment of various disorders.